Carbon dioxide sequestration by mineral carbonation using electric arc furnace slag - Ogakwu, Omale Sunday (2020)
Fossil fuel usage is the primary source of anthropogenic air pollution, where carbon dioxide (CO2) is the most prominent agent that contributes to global climate change. The iron and steel industries are major contributors to gaseous CO2 emission. These industries also produce solid wastes in the form of slags during operations. Steelmaking in electric arc furnace (EAF) generates between 10-15% slag wastes per ton of steel production, which can be used in mineral carbonation to capture and store CO2. In this study, the EAF slag from an iron and steelmaking factory in Klang, Malaysia, was utilized for the CO2 sequestration through both direct aqueous and indirect mineral carbonation method in a batch reactor. The direct aqueous carbonation investigation was at room temperature, and different solid/liquid ratio, pressure, and time. The indirect carbonation was performed, after the extraction of essential metallic ions from the EAF slag at a different temperature, solvent concentration, and solid/liquid ratio. The direct aqueous mineral sequestration capacity was 58.36±5.84g CO2/kg of slag under room temperature after 3 hr, solid/liquid ratio of 1:5, and using < 63 μm particle size. The sequestration efficiency was 28.11 %, and the degree of carbonation was 23.30 % at the pressure of 5 bars. The shrinking core model shows that the direct aqueous carbonation was by the ash layer product phase-controlled, with the regression coefficient (R2) of 0.97. In the dissolution of essential metallic ions like Ca, Mg, and Fe, the slag from EAF was the source. The dissolution efficiency was affected by temperature, solvent concentration, solid/liquid ratio, and reaction time. At the temperature of 75 oC, Ca ion was extracted from the slag with 86.46 % efficiency and Mg ion of 30.13 % after 1 hr of using 0.22 M HCl. However, the dissolution in the solid/liquid ratio of 10 g/l was higher than 20 g/l and 30 g/l. The dissolution of Ca ion was 80.27 %, 61.33 %, and 50.53 %, and that of Mg ion was 26.63 %, 24.20 %, and 22.16 %, respectively, after 1 hr in 0.22 M HCl. The acid concentration of 0.44 M extracts more Ca, Mg and Fe ions than 0.33 M and 0.22 M. The efficiency after 1 hr.; at 35℃ from 20 g/l was 68.84 %, 65.63 %, 61.33 % for Ca, and 27.52 %, 26.40 %, 24.20 % of Mg, while that of Fe from 20 g/l was 10.09 %, 8.76 %, and 5.18 % respectively. Meanwhile, in the indirect carbonation, the dissolved Ca ion was used for the formation of calcium carbonate through CO2 sequestration. The formed precipitate calcium carbonate (PCC) of 98.61 ± 1 % purity, and the sequestration capacity of 0.4105 ± 0.195 kg of CO2/kg of CaCO3 within 1 hr was achieved. This shows that at moderate conditions (0.22 M HCl, 35℃, and 1 hr), both CO2 sequestration and calcium carbonate of high purity were realized. In a reaction of a heterogeneous solid-liquid mixture, the modified shrinking core model was appropriate. The modified shrinking core model best interpreted the kinetics behavior for all the parameters studied in the dissolution of Ca ion from the EAF slag. From the regression coefficient (R2), the dissolution was controlled by the product layer phase. The order of reaction for acid concentration and S/L ratio was 0.31419 and -1.02459 respectively. The activation energy of the process over the temperature range was, calculated to be Ea = 3.881KJ/mol From the results of the two sequestration methods, the indirect route was better with a higher sequestration capacity and calcium carbonate of high purity. The EAF slag demonstrated the potential and available material for both CO2 sequestration and economic purposes, instead of being landfilled.